2022
DOI: 10.3389/fchem.2022.996079
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, docking studies, biological activity of carbon monoxide release molecules based on coumarin derivatives

Abstract: In the present work, we synthesized seven complexes. All complexes were identified by ESI-HRMS, 1H-NMR, 19F-NMR and 13C-NMR spectroscopies. The synthesized complexes were tested for their anticancer activities in vitro against three different human cell lines, including breast MDAMB231, cervical Hela, liver HepG2. IC50 values of complexes 1-7 were 34.98–667.35 µM. Complex 5 revealed higher sensitivity towards MDAMB231 cells with IC50 values 34.98 μM in comparison to 5-FU as positive control. Moreover, complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Considering the scientific evidence and proven relevance of coumarin derivatives as modulators of the Nrf2 signaling pathway to increase endogenous antioxidant defense and promote several pharmacological properties, several studies have been performed to design and synthesize new coumarin derivatives able to activate Nrf2 signaling and its antioxidant response, including oximes bearing coumarin derivatives [165], chalcone-coumarin hybrid compounds [166], coumarin-derived imino sulfonates [167], carbon monoxide release coumarin complexes [168], and coumarin-containing hybrids [9][10][11][12]. Coumarins have special physicochemical properties, such as π-π conjugation, low molecular weight, simple chemical structure, high bioavailability, and solubility, rich in electrons and charge properties, which could bind to many targeted proteins to produce a wide range of biological activities [6,7,168]. Moreover, coumarin derivatives have low toxicity and high versatility for synthetic transformation into a variety of functionalized derivatives, ensuring them a prominent role as lead compounds in drug design and development [6,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the scientific evidence and proven relevance of coumarin derivatives as modulators of the Nrf2 signaling pathway to increase endogenous antioxidant defense and promote several pharmacological properties, several studies have been performed to design and synthesize new coumarin derivatives able to activate Nrf2 signaling and its antioxidant response, including oximes bearing coumarin derivatives [165], chalcone-coumarin hybrid compounds [166], coumarin-derived imino sulfonates [167], carbon monoxide release coumarin complexes [168], and coumarin-containing hybrids [9][10][11][12]. Coumarins have special physicochemical properties, such as π-π conjugation, low molecular weight, simple chemical structure, high bioavailability, and solubility, rich in electrons and charge properties, which could bind to many targeted proteins to produce a wide range of biological activities [6,7,168]. Moreover, coumarin derivatives have low toxicity and high versatility for synthetic transformation into a variety of functionalized derivatives, ensuring them a prominent role as lead compounds in drug design and development [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Based on other coumarin derivative's chemical structures, structure-activity relationship analysis demonstrated that chemical modification at C-6, C-7, and C-8 as well as the presence of an α,β-unsaturated carbonyl group or free hydroxyl at C-8 increases antiinflammatory activity, including intestinal anti-inflammatory properties when compared with no substituted coumarins [84,168,171].…”
Section: Discussionmentioning
confidence: 99%
“…Liu and coworkers synthesized seven complexes, incorporating coumarin ligands and carbonyl cobalt with the aim of producing potential anticancer agents with the ability to release carbon monoxide ( Liu et al, 2022 ). Antiproliferative activity of the novel compounds was tested against Hep2G, HeLa, and MDA-MB-231 tumor cell lines (MTT assay, 10 μM–150 μM concentrations, 24 h incubation, 5-fluorouracil (5-FU) as a positive control).…”
Section: Coumarin Complexes With Anticancer Activitymentioning
confidence: 99%